2019
DOI: 10.1080/00401706.2019.1638834
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Variable Approach to Gaussian Process Modeling with Qualitative and Quantitative Factors

Abstract: Computer simulations often involve both qualitative and numerical inputs. Existing Gaussian process (GP) methods for handling this mainly assume a different response surface for each combination of levels of the qualitative factors and relate them via a multiresponse cross-covariance matrix. We introduce a substantially different approach that maps each qualitative factor to an underlying numerical latent variable (LV), with the mapped value for each level estimated similarly to the correlation parameters. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 21 publications
2
90
0
Order By: Relevance
“…The key idea of the LVGP approach is to map the qualitative factors into low-dimensional quantitative latent variable (LV) representations. Our study 28 showed that the LVGP modeling dramatically outperforms existing GP models with qualitative input factors in terms of predictive root mean squared error (RMSE). In addition to empirical evidence of far better RMSE predictive performance across a variety of examples, the LVGP approach has strong physical justification in that the effects of any qualitative factor on a quantitative response must always be due to some underlying quantitative physical input variables (otherwise, one cannot code the physics of the simulation model) 28 .…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The key idea of the LVGP approach is to map the qualitative factors into low-dimensional quantitative latent variable (LV) representations. Our study 28 showed that the LVGP modeling dramatically outperforms existing GP models with qualitative input factors in terms of predictive root mean squared error (RMSE). In addition to empirical evidence of far better RMSE predictive performance across a variety of examples, the LVGP approach has strong physical justification in that the effects of any qualitative factor on a quantitative response must always be due to some underlying quantitative physical input variables (otherwise, one cannot code the physics of the simulation model) 28 .…”
Section: Introductionmentioning
confidence: 84%
“…Our study 28 showed that the LVGP modeling dramatically outperforms existing GP models with qualitative input factors in terms of predictive root mean squared error (RMSE). In addition to empirical evidence of far better RMSE predictive performance across a variety of examples, the LVGP approach has strong physical justification in that the effects of any qualitative factor on a quantitative response must always be due to some underlying quantitative physical input variables (otherwise, one cannot code the physics of the simulation model) 28 . Noting that the underlying physical variables may be extremely highdimensional (which is why they are treated as a qualitative factor in the first place), the LVGP mapping serves as a low-dimensional LV surrogate for the high-dimensional physical variables that captures their collective effect on the response.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The standard GP methods were developed under the premise that all input variables are quantitative, which does not hold in many real engineering applications. We recently proposed a latent variable Gaussian processes (LVGP) [25] modeling method that maps the levels of the qualitative factor(s) to a set of numerical values for some latent quantitative variable(s). The latent variables transform the underlying high dimensional physical attributes associated with the categorical variables into the latent-variable space and quantify the "distances" between samples.…”
Section: Latent Variable Gp Modelling For Mixed-variable Problemsmentioning
confidence: 99%